(untitled) (International journal of medical sciences, 2026)
Aging populations are associated with a marked rise in the number of patients seeking care from primary physicians for urological conditions. Among individuals aged 65 years and older, urological complaints represent the third most frequent category of medical concern and contribute, at least in part, to approximately 47% of outpatient visits. Common andrological and urological conditions in this age group include Lower Urinary Tract Symptoms (LUTS), Benign Prostatic Hyperplasia (BPH), acute urinary retention, genitourinary malignancies, urinary tract infections, urolithiasis, and various forms of sexual dysfunction. These disorders exert a substantial negative effect on patients’ quality of life, often resulting in reduced physical mobility, sleep disturbances, and increased risk of social isolation.